PARTICIPATORY PROJECT DESIGN AND ITS EFFECTIVENESS IN GOVERNMENT-FUNDED PARISH DEVELOPMENT PROJECTS: A KABALE DISTRICT CASE STUDY - Nambale , Esther Akinyi; Josephine , Grace Otieno (Current Journal of Human Resource Management (CJHM), 2024)
This study investigates the impact of participatory project design on the success of government-funded projects, specifically focusing on parish development in Kabale District, Uganda. Utilizing a cross-sectional survey with 75 respondents, the study integrated both quantitative and qualitative analyses. The research employed descriptive, bivariate, and multivariate analytical methods to assess the relationship between participatory design and project success. A Pearson correlation matrix was used to examine bivariate correlations, and linear regression was applied to analyze the impact of participatory design on project success. The results indicate a significant positive effect of participatory project design on the effectiveness of parish development projects (coef = -0.780, p-value = 0.000). This suggests that a participatory approach is crucial for enhancing project success. The study concludes that participatory project design significantly influences project success in Kabale District and recommends focusing on defining project goals, identifying risks, and refining strategies to ensure the sustainability of parish development projects